Dockerized Application with Web Interface - Abhishek M Nair; Sivaiswarya CK; Sidharth S; Visakh KK; Jibin Joy (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Developing an application can be a task if any kind of conflict arises during deploying the code or while running them and it can be due to the storage or the code being not supported by the other party’s system. Thus to provide a solution for this matter, we are introducing the project concept of Dockerized application deployment through a web interface. This proposed project combines the efficiency of Docker containers with a web interface to create a platform for running and managing applications easily. When a programmer or a developer or anyone in the field of programming has conflict in uploading, running or deploying their application code from another programmer’s system to their own due to the inefficiency or lack of facilities in their system, they can use this web interface as a solution. Especially during the time of any rush, they can opt for this web interface as it does not require the installation of a local Docker software and any extra dependency management, as installation of Dockers are a bit time lagging. One of the main factors of this project is that this web interface can be run in any kind of computer system without any extra facilities being added to it. Whether the system is less efficient or high efficient regardless of the type of the system, this web interface is easy to access for the users. Users can upload their application code, build Docker images, and run them directly from the web interface. With the advantage of Docker’s utility methodologies for shipping, testing and deploying code, you can reduce the delay between writing codes and running applications .It has additional features like users can define environment variables for their applications, configure network settings for container communication ,mount persistent volumes to store application data with help of virtual cloud, implement user roles and permissions for secure access control .The front end of the web page is created using NEXT Programming Language meanwhile the backend is applied using NEXT, Docker and Python Flask API. About NEXT Programming Language that in this language, when the front-end is applied the backend function gets directly deployed making us use less effort in creating the webpage. It's a newly created advanced programming language. Overall, this Dockerized application deployment web-interface offers a user-friendly and efficient solution for developers, system administrators, and DevOps teams, streamlining the application development and deployment process.
Keywords: Docker; Shell Access; Static/File Hosting; Log Analyser